Implementation of Service Information System Integration at Regional General Hospital in Pekanbaru as a Step Towards a Smart Hospital - Wasiah Sufi; Ridho Ramadhan Arfi; Alexsander Yandra; Ira Oktaviani Rz (Poltekkes Kemenkes Riau, 2026)
Digitalization of hospital services is a strategic necessity to improve effectiveness, efficiency, and patient safety. RSUD Arifin Ahmad Hospital in Pekanbaru, as a provincial referral hospital, faces complex inter-unit service processes, making digital transformation imperative. This study addresses a gap in the literature by emphasizing the integration of inter-unit services, which is often overlooked in the transition toward a smart hospital. Employing a qualitative method with a case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that digitalization accelerates service delivery, enhances data accuracy, strengthens coordination, and reduces administrative burdens, although its success is influenced by infrastructure quality, human resource readiness, SIMRS integration, and organizational culture. These findings underscore that digitalization is a fundamental foundation for realizing a modern, patient safety–oriented smart hospital.